2018
DOI: 10.1002/jssc.201701082
|View full text |Cite
|
Sign up to set email alerts
|

Determination of ultraviolet filter compounds in environmental water samples using membrane‐protected micro‐solid‐phase extraction

Abstract: A method based on membrane-protected micro-solid-phase extraction coupled with gas chromatography and mass spectrometry was developed for the determination of six ultraviolet filter compounds in various aqueous media. Multiwalled carbon nanotubes as the sorbent were encapsulated in a sealed polypropylene membrane packet and immersed in the sample to extract the analytes, and then dichloromethane was used for desorption purpose. The method was sensitive enough for quantitative analysis of the target analytes, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…The LOD and LOQ calculated as three and ten standard deviations of the background noise, respectively, were in the range of 1.2-4.7 μg/L and 4.0-15.6 μg/L, much smaller than the 580 and 1 700 μg/L achieved for the determination of MePB by off-line preconcentration and HPLC-UV analysis [18]. Most studies described the use of HPLC with MS detection for the analysis of these PCPs compounds in water [5,9,[13][14][15] [51], which were similar to those described in the present study. The LODs allowed in this work were also comparable to concentrations found for PCPs in wastewater samples [9].…”
Section: Analytical Performancementioning
confidence: 99%
See 2 more Smart Citations
“…The LOD and LOQ calculated as three and ten standard deviations of the background noise, respectively, were in the range of 1.2-4.7 μg/L and 4.0-15.6 μg/L, much smaller than the 580 and 1 700 μg/L achieved for the determination of MePB by off-line preconcentration and HPLC-UV analysis [18]. Most studies described the use of HPLC with MS detection for the analysis of these PCPs compounds in water [5,9,[13][14][15] [51], which were similar to those described in the present study. The LODs allowed in this work were also comparable to concentrations found for PCPs in wastewater samples [9].…”
Section: Analytical Performancementioning
confidence: 99%
“…In wastewater effluents, B‐3 has been reported in concentrations from 5 to 10 400 ng/L . Concentrations of MePB and PrPB in wastewater effluent have been described from 69 to 3142 ng/L , and in other studies have been found in even higher concentrations from 14.24–15.22 μg/L and 23.59–24.14 μg/L, respectively . Thus, the effective environmental monitoring of PCPs in aqueous environmental matrices is required due to the absence of stringent regulation specific to these contaminants in water, as well as their possible adverse impacts on the environment and human reproductive health .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…UVFs have been determined in waters by LC‐UV [6,25,26], LC–MS/MS [15,27,28], and UHPLC–MS/MS [6,29–31], in addition to GC–MS with an additional derivatization step [6,32,33] and GC–MS/MS [34].…”
Section: Introductionmentioning
confidence: 99%
“…HPLC and GC coupled with MS have been employed to analyze these analytes from real samples . A variety of sample preparation techniques have been exploited before chromatographic separation for the extraction and preconcentration of these analytes.…”
Section: Introductionmentioning
confidence: 99%